2019
DOI: 10.1371/journal.pone.0216614
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin does not improve disease severity in acute experimental pancreatitis

Abstract: Acute pancreatitis is a severe systemic disease triggered by a sterile inflammation and initial local tissue damage of the pancreas. Immune cells infiltrating into the pancreas are main mediators of acute pancreatitis pathogenesis. In addition to their antimicrobial potency, macrolides possess anti-inflammatory and immunomodulatory properties which are routinely used in patients with chronic airway infections and might also beneficial in the treatment of acute lung injury. We here tested the hypothesis that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…This is also one of the well-established methods for IHC quantification in several publications. [57][58][59][60] We have been trying to quantify by using staining intensity or IDO value. However, because chondrocytes only accounts for around 5% of the cartilage area, it would bring us much background signal for quantification.…”
Section: Discussionmentioning
confidence: 99%
“…This is also one of the well-established methods for IHC quantification in several publications. [57][58][59][60] We have been trying to quantify by using staining intensity or IDO value. However, because chondrocytes only accounts for around 5% of the cartilage area, it would bring us much background signal for quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Weis et al 41 in their experimental work on mice confirmed that the prophylactic use of macrolide antibiotics does not reduce the severity of the disease in the course of acute pancreatitis and does not reduce the migration of cytokines to the pancreatic tissue in the acute stage of the disease (Table 1). Numerous studies have confirmed that the use of antibiotics only in the case of infected necrosis can have the benefit of inhibiting or reducing the systemic inflammatory cascade in acute pancreatitis.…”
Section: Experimental Treatmentmentioning
confidence: 95%
“…In mice, an AP can be induced as mild or severe form depending on number and days of CN injections [27]. In our study, AP was induced using an adapted mouse model of CN-induced mild acute pancreatitis, as previously described [28][29][30][31][32]. Prior to injection of CN or saline, mice were fasted for 14-16 h with free access to water.…”
Section: Animal Experimentsmentioning
confidence: 99%